2015
DOI: 10.1039/c4md00471j
|View full text |Cite|
|
Sign up to set email alerts
|

Application of QM/MM and QM methods to investigate histone deacetylase 8

Abstract: Computational chemistry plays an important supporting role in the early stages of drug discovery research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Only atoms within 15 Å of DMM substrate were treated flexibly during the QM/MM calculations, except for those atoms that crossed the QM/MM interface. 45,55 The density functional theory (DFT) M06 functional 56 corresponding to the expected bond breaking/forming process under investigation. Single point QM/MM energy calculations were performed using the 6-311+G(d,p) basis set for H, C, N, O and S atoms and TVZP for Mn (∆Ε SP-HL).…”
Section: Qm/mm Calculationsmentioning
confidence: 99%
“…Only atoms within 15 Å of DMM substrate were treated flexibly during the QM/MM calculations, except for those atoms that crossed the QM/MM interface. 45,55 The density functional theory (DFT) M06 functional 56 corresponding to the expected bond breaking/forming process under investigation. Single point QM/MM energy calculations were performed using the 6-311+G(d,p) basis set for H, C, N, O and S atoms and TVZP for Mn (∆Ε SP-HL).…”
Section: Qm/mm Calculationsmentioning
confidence: 99%
“…This structural evidence, in conjunction with steady-state kinetic experiments on Danio Rerio CD1 and CD2, suggested that such vicinal histidines are crucial for catalysis in HDAC6, in analogy with histidines in other widely studied HDACs belonging to the class I ( e.g. , HDAC8, HDAC2, and HDAC3) . For example, in the case of HDAC8, the vicinal His142 and His143 act as general base and acid, respectively, for the activation (via deprotonation) of the nucleophilic water molecule and for the release (via protonation) of the amine product, ultimately released from the enzyme. , Indeed, the structural similarities among all HDACs suggested that the catalytic mechanism for HDAC6 is analogous to that of other HDACs.…”
Section: Introductionmentioning
confidence: 89%
“…In this context, it is also important to emphasize that HDAC6 is unique in the HDAC family, as it is a heterodimeric structure with two different catalytic domains, namely CD1 and CD2. Intriguingly, the specific biological relevance of each domain is still not fully understood, although CD2 has been proposed as the most promising target domain for the development of drugs for several diseases. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is much more challenging to simulate metalloproteins based on the empirical MM techniques, so, higher level theoretical models to investigate of protein–ligand binding, and also reactivity, are needed. Gleeson and Gleeson [194] employed hybrid QM/MM methods to study substrate binding and reactivity at HDAC8, which has a putative pathogenic role in neurological conditions including AD and FRDA. The aim of this study was to develop and validate QM and QM/MM HDAC8 models for predicting new Zn binding moieties, and especially analyzing the interactions between new inhibitors and HDAC proteins that are suboptimally described by traditional molecular mechanic methods.…”
Section: Qm/mm Studymentioning
confidence: 99%